Oral Haloperidol or Risperidone Treatment in Rats: Temporal Effects on Nerve Growth Factor Receptors, Cholinergic Neurons, and Memory Performance - Terry, Alvin V. (2007)
First and second generation antipsychotics (FGAs and SGAs) ameliorate psychotic symptoms of schizophrenia, however, their chronic effects on information processing and memory function (i.e., key determinants of long term functional outcome) are largely unknown. In this rodent study the effects of different time periods (ranging from two weeks to six months) of oral treatment with the FGA, haloperidol (2.0 mg/kg/day), or the SGA, risperidone (2.5 mg/kg/day) on a water maze repeated acquisition procedure, the levels of nerve growth factor receptors, and two important cholinergic proteins, the vesicular acetylcholine transporter and the high affinity choline transporter were evaluated. The effects of the antipsychotics on a spontaneous novel object recognition procedure were also assessed during days 8-14 and 31-38 of treatment. Haloperidol (but not risperidone) was associated with impairments in water maze hidden platform trial performance at each of the time periods evaluated up to 45 days, but not when tested during days 83-90. In contrast, risperidone did not impair water maze task performance at the early time periods and it was actually associated with improved performance during the 83-90 day period. Both antipsychotics, however, were associated with significant water maze impairments during the 174-180 day period. Further, haloperidol was associated with decrements in short delay performance in the spontaneous novel object recognition task during both the 8-14 and 31-38 periods of treatment, while risperidone was associated with short delay impairment during the 31-38 day time period. Both antipsychotics were also associated with time dependent alterations in the vesicular acetylcholine transporter, the high affinity choline transporter, as well as TrkA, and p75 neurotrophin receptors in specific brain regions. These data support the notion that while risperidone may hold some advantages over haloperidol, both antipsychotics can produce time-dependent alterations in neurotrophin receptors and cholinergic proteins as well as impairments in the performance of tasks designed to assess spatial learning and episodic memory.